If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5r + -6 + 4r = 2 Reorder the terms: -6 + -5r + 4r = 2 Combine like terms: -5r + 4r = -1r -6 + -1r = 2 Solving -6 + -1r = 2 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1r = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -1r = 2 + 6 -1r = 2 + 6 Combine like terms: 2 + 6 = 8 -1r = 8 Divide each side by '-1'. r = -8 Simplifying r = -8
| X/3-19=-21 | | -12+5=12-19 | | z/6+2=4-z/6 | | 4^2-(-5^2)/45+5 | | 2=v-(-3) | | -1/2x-5=15 | | 2x^2+5=5x^2-27 | | X+11+x+11=104 | | f/m=a | | 8-3(m-4)=2m | | w=7.5h | | 7x+7=6x+6 | | -16(x+1)=608 | | -3(2+n)=9 | | 41=8m-15 | | -265-(190)= | | (-4)+5/3 | | 18+3n=3+7+5n | | (x^3-16^2+64)/(x^3-8x^2) | | 9p-18=27 | | 2(x-3)=3(x+2)-3 | | 10(-11-4p)-2p=(-1-3p) | | (5x^3-9x^2+5)-(5-9x^2+5x^3)= | | -5(x-1)+x=6x-5 | | 7p+4=7-2p | | 7x+3(6x+3)=184 | | f(x)=x^2+6x-10 | | 2(675+80n)=2310 | | p/9-5=7 | | x/4-2=5/6+x-4/3 | | (10w-1)(10w+1)=20w | | 6y+2=3y-3 |